PENGARUH PERNIKAHAN DINI TERHADAP PENDIDIKAN DI DESA ANGKATAN KEPULAUAN KANGEAN MADURA - Misana Yatus Syafaa; Marta Hilde Hutabalian; Clareza Arum Anugeraheni; Katerina Bataha (Journal Publicuho, 2021)
Kangean is the name of an archipelago at the eastern end of the Regency. The very high rate of early marriage is one of the main reproductive problems facing this region. Many people do not understand the consequences of early marriage. Early marriage is effective in preventing adultery, but early marriage is prone to divorce, early marriage makes education stop. The method we use is a qualitative method and the data collection techniques we use are interviews and literature review by using the object of study on the pattern of people's lives in the village of Forces, Arjasa sub-district, Sumenep regency. The purpose of this research is to add insight about the effect of early marriage on education. The results of our research from 25 respondents, most of them have done early marriage because the parents' desire is very big to marry off their children so that their responsibilities as parents will reduce their responsibilities, this area is very far from urban areas so there is minimal information about the bad consequences of marriage. early. due to the cessation of education will cause the younger generation to lose their future.